High/low‐volume center experience predicts outcome of AMS 800 in male stress incontinence: Results of a large middle European multicenter case series. Issue 6 (22nd June 2020) - Queissert, Fabian; Hüsch, Tanja; Kretschmer, Alexander; Anding, Ralf; Kirschner‐Hermanns, Ruth; Pottek, Tobias; Olianas, Roberto; Friedl, Alexander; Homberg, Roland; Pfitzenmaier, Jesco; Naumann, Carsten M.; Nyarangi‐Dix, Joanne; et al.
Abstract: Aim: To analyze the influence of implantation volume of artificial sphincters (AMS 800) on outcome in a large central European multicenter cohort study. Methods: As part of the DOMINO (Debates on Male Incontinence) project, the surgical procedures and outcomes were retrospectively analyzed in a total of 473 patients who received an artificial sphincter (AMS 800) between 2010 and 2012. Clinics that implanted at least 10 AMS 800 per year were defined as high‐volume centers. Results: Sixteen centers had a mean rate of 9.54 AMS 800/y of which five clinics were identified as high‐volume centers. They implanted significantly more double cuffs (55% vs 12.1%; P  < .001), used the perineal approach significantly more often (78% vs 67.7%; P  = .003) and chose larger mean cuff sizes (4.63 cm vs 4.42 cm; P  = .002). With a mean follow‐up of 18 months, the revision rate was significantly higher at low‐volume centers (38.5% vs 26.7%; P  = .037), urethral erosion being the main reason for revision. Social continence (0‐1 pads/24 h) was achieved significantly more often in high‐volume centers (45.5% vs 24.2%; P  = .002). Conclusions: Our study showed significantly better continence results and lower revision rates at high‐volume centers, confirming earlier results that are still true in this decade. We, therefore, recommend surgery for male incontinence at qualified centers.